Analisis Pengaruh Strategi Knowledge Management terhadap Efisiensi Kerja Karyawan - Gaby Novryma Pakiding; Augie David Manuputty (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
This study aims to determine the conditions of the implementation of knowledge management strategies and identify the effect of knowledge management on employee work efficiency at PT. Asuransi Sinar Mas. Reason being that knowledge management strategy is very needed by a company to increase profits and company assets, especially human resources. Before knowing how much influence knowledge management has on the work efficiency of employees, it is first necessary to test the conditions of the implementation of knowledge management strategies that are being run in the company. In this study, the researcher used a quantitative method by collecting data distributed to 35 respondents as a sample to get primary data. Then for the measurement method, the researcher used a likert scale and merged knowledge management strategies with quality factors from the European Foundation for Quality Management (EFQM). From the likert scale calculation and the 4.10 results obtained where this is considered good, to test the quality of the application of knowledge management as a whole a percentage of 77.9% was acquired where it can be said to be good, then for the level of influence of knowledge management strategies on employee work efficiency is 77.6% or in other words, knowledge management affects employee work efficiency. Although the figures obtained are good enough, there is still a need for the company to make improvements so it can compete with other companies.